The Politics of Population Control: Family Planning and Poverty Alleviation in West Aceh, Indonesia - Latif, Ikhwan Rahmatika; Panjaitan, Debora; Ikhsan, Ikhsan; Alqarni, Wais; Ilhamsyah, Fadhil (Journal of Contemporary Local Politics, 2025)
- This study investigates the political dynamics of population control in West Aceh Regency and their influence on local poverty reduction efforts. Using a qualitative case study approach in the Johan Pahlawan and Meureubo sub-districts, the research collected primary data through in-depth interviews with 24 purposively selected informants—including health officials, family planning cadres, community leaders, and couples of reproductive age—alongside field observations and document analysis. Thematic content analysis was employed to identify patterns related to service access, actor influence, and community engagement. Theoretically, the study draws on structural poverty theory, responsive public policy theory, local political theory, and program effectiveness theory. Findings indicate that high levels of education, access to information, and community-based cadre strategies contribute to strong program participation in urban areas. In contrast, semi-rural regions face compounded barriers due to weak infrastructure, policy fragmentation, and cultural opposition. Local politics critically shape program outcomes; actors such as religious leaders and village elites mediate acceptance through moral and ideological framing. Additionally, the lack of male involvement undermines the program’s transformative potential. The study concludes that population control should not be treated as a standalone administrative effort but must be embedded within a decentralized, inclusive welfare policy tailored to local realities. Policy implications include the need for cross-sectoral program integration, culturally sensitive outreach, male-targeted reproductive education, and flexible budgeting frameworks that allow sub-district-level policy adaptation. These measures are essential to position family planning as a viable instrument for equitable poverty reduction in West Aceh.